EFEKTIVITAS PENYIDIKAN TINDAK PIDANA PENAMBANGAN EMAS TANPA IZIN DI KABUPATEN SOLOK SELATAN (Studi pada Direktorat Reserse Kriminal Khusus Kepolisian Daerah Sumatera Barat) - Pamungkas, Darmadi Prapto (LPPM Universitas Ekasakti Padang, 2018)
Indonesia is the rich country of mine, such as gold, silver, petroleum, mine, etc. Management of mine should be done by government or private. Every mining company obligated to get license as regulated in the Regulation Number 4 Year 2009 about Mineral Mining Juncto the Government Regulation Number 23 Year 2010 about the Implementation of Mineral Mining. In fact, not all companies have license. There are so many companies operate illegal. One of them is gold mining without license (PETI). The specification of the research is descriptive analytic. The methods used are normative as primary approach and juridical empiric method as secondary approach. The sources of data are secondary and primary. The techniques of collecting data uses field study by interviewing for the primary data and library study for the secondary data. Then, the data analyzed qualitatively in descriptive qualitative form. From the research results obtained several conclusions: First, the effective of investigation gold mining without license by Directory of Reserve Special Criminal of West Sumatera Police based on the data got can be seen clearly effective because from 3 (three) cases all has been investigation and submitted to Court. Second, the obstacles faced by Directory of Reserve Special Criminal of West Sumatera Police in executing of gold mining without license (PETI) in South Solok Regency consist of: (a) no synergy in supporting the law enforcement together between instances and other because the agents of gold mining without license (PETI) are backed up by law enforcer, government until traditional viewers; and (b) limited tool such as no double garden cars or boat to reach field and no communication satellite which can be operated in the unreached location by phone signal.